Do Socially Responsible Firms Pay Their Right Part of Taxes? Evidence from the European Union - Fourati, Yosra Makni; Affes, Houda; Trigui, Ikram (Journal of Applied Business and Economics, 2019)
This study extends the literature by examining the relationship between the corporate social responsibility (CSR)and tax avoidance. Based on a sample of 614 companies from 15 European-Union countries over the period of 2002-2015, we find that, on average, socially responsible firms are more involved in tax avoidance activities than the less responsible ones. In addition, we investigate how different CSR activities affect corporate tax avoidance. More interestingly, our results show that a strong activity in the economic, environmental, social and corporate-governance dimensions is associated with a high level of tax avoidance, indicating that CSR and tax avoidance are complementary strategies.